making a peoples defense and safety System - Herianto, Novi; Nakir, M. (Advances in Social Sciences Research Journal, 2020)
Article 30 of the 1945 Constitution is the basis for the formulation and drafting of Law No.3 / 2002 on national defense. In article 30, it is stipulated that national defense and security efforts are carried out through the system of defense and security of the total people by the Indonesian National Army and the Indonesian National Police, as the main force, and the people, as the supporting force. This system of defense and security for the people of the universe is then manifested in Law No.20 / 1982 concerning the main provisions of national defense. However, when the TAP MPR Number VI and Number VII was issued regarding the Separation of the Police from ABRI. The government is drafting a new Defense Law that is aligned to separate Defense and security that is adaptive to these changes. The defense is compiled and formulated and then translated into Law no. 3/2002, however, the Law on Security was not immediately realized, instead Law No.2 / 2002 concerning the Indonesian National Police. Until now, the Law on Security does not exist and has not been materialized. As a result, there is a gap between legislation in the defense sector and legislation in the security sector. Some of the mandates of Law No.3 / 2002 can then be translated into Laws, Government Regulations, Presidential decrees instead other legislation products to support national defense. The lack of this security aspect of course affects the defense and security system which was previously manifested as a comprehensive unit which is of course adjusted to the history of the nation itself. In addition to defense duties which are military in nature, there are tasks in the field of military Nir which all fall into the category of security aspects. As long as there are no regulations governing Security, the Defense and Security System mandated in the 1945 constitution will never materialize.